Petrogenesis and tectonic setting of Neoarchean K-rich granitoids in the Zhulagou area: Implications for the crustal maturation of Yinshan Block, western North China Craton - Xiao Wang; Jin Liu; Hai Zhou; Xiaoguang Liu; Chenying Yu; Shuhui Zhang; Jian Zhang (Geosystems and Geoenvironment)
K-rich granitoids are considered as an indicator of the maturation of the continental crust, particularly in correlation to the significant crustal evolution during the Neoarchean Eon. The Yinshan Block, a typical Neoarchean microcontinental block of the western North China Craton (NCC), preserves several typical K-rich granites (monzogranitic gneisses). However, their petrogenesis and tectonic background of these remain unclear, hindering our understanding of the late Neoarchean crustal evolution of the NCC. This study presents new geochronological, geochemical, and Sr-Nd-Pb-Hf isotopic data on the K-rich granites exposed in the Zhulagou area, a key exposure of the Yinshan Block. Zircon U–Pb dating results suggest that the K-rich granites were emplaced at 2.52–2.50 Ga. The K-rich granites exhibit high SiO2 (68.70–74.10 wt. %) and K2O (3.40–7.79 wt. %) and lower MgO (0.24–1.04 wt. %) content. They also have high Sr/Y and (La/Yb)N ratios, as well as low Y and Yb contents. Furthermore, they display variable εHf(t) (–1.1 to +2.5) and εNd(t) (–6.05 to +1.64) values, with relatively low Pb isotopes (206Pb/204Pb(t) = (13.910485–15.241164), 207Pb/204Pb(t) = (14.806723–15.259938), and 208Pb/204Pb(t) = (33.758621–35.592727)), indicating that their parental magmas may have originated from the partial melting of a thickened lower crust with heterogeneous sources. Combined with previous data, we suggest that a pulse or stage of mantle plume may have been operating under the Yinshan Block during late Neoarchean period. The pre-existing thickened (mafic) lower crust was partially melted to generate these K-rich granites at 2.52–2.50 Ga, resulting in a mature and stable continental crust.